The Sharing Economy in Europe: From Idea to Reality - Cristina Miguel; Gabriela Avram; Andrzej Klimczuk; Bori Simonovits; Bálint Balázs; Vida Česnuitytė (The Sharing Economy in Europe: Developments, Practices, and Contradictions, 2022)
This chapter explains the rationale behind the book. It provides basic definitions of the concept of the sharing economy as well as the primary meanings related to the subject of the analysis undertaken in the subsequent chapters. This Introduction also includes a description of the main benefits of the analysis of the sharing economy from a European perspective. It highlights that the idea of the book emerged from the collaboration of most co-authors in the COST Action CA16121 'From Sharing to Caring: Examining Socio-Technical Aspects of the Collaborative Economy.' Finally, the outline of the book is presented, providing a description of the content of each chapter within this academic collection.
Keywords: D16; L86; Z18; Z13; 330; Collaborative Consumption; Collaborative Economy; Peer-to-Peer Economy; Digital Platforms; Sharing Economy